Study on preparation and influencing factors of coal gangue fill slurry material - Ping Liu; Zhenzhi Liu; Zhen Lu; Yanqing Guo; Yueqin Qiu (Case Studies in Construction Materials)
The large quantity of coal gangue will become an increasingly serious part of environmental pollution. However, it can be aggregated with water and fly ash to form a slurry with a stabile rheology that can be used to fill underground mining areas to reduce environmental pollution. In this study, an orthogonal test scheme was formulated, and the significance of the influence of test factors on the test index was judged using variance analysis and range analysis. By analyzing the effects of mass concentration, fly ash percentage, and aggregate grade on the rheology and stability of the slurry, a fill slurry that meets the requirements of reasonable indexes was developed. Finally, the diffusion effect of the prepared slurry was explored using a simulation. The results show that the mass concentration had the strongest effect on the plastic viscosity, yield stress, extensibility, water secretion rate, and segregation rate of the gangue slurry. The effect of aggregate gradation on the yield stress, water secretion rate, and segregation rate of slurry was stronger than that of the fly ash content, while the effect of the fly ash content on the plastic viscosity and extensibility of the slurry was stronger than that of the aggregate gradation. With the increase in mass concentration and the content of fine particles in the aggregate, the plastic viscosity of the slurry increased, the slump extension decreased, and the fluidity decreases while the yield stress increased, the water secretion rate and segregation rate decreased, and the stability increased. The optimal ratio of the slurry was determined to be 70 % mass concentration, 10 % fly ash, and an aggregate grading consisting of 80.34 % 0–1 mm particles, 12.95 % 1–3 mm particles, and 6.71 % 3–5 mm particles. The flow and diffusion effect of the optimized gangue slurry in the mining area was observed through an image and stress data acquisition system, and it was determined that the slurry could well be filled into the rock voids in the mining area. The results of the study can provide some theoretical basis for the preparation of slurry to fill hollow zones.